PENGARUH MODAL KERJA DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gusri Ermila; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of Working Capital and Capital Structure on the Profitability of Food and Beverage Industries listed on the Stock Exchange. This study uses two indenpendent variables and one depandent variable, namely working capital and capital structure as indenpendent variables and profitability as the dependent variable. The research method used is descriptive quantitative using the program SPSS. The sampling method used was purposive sampling and obtained 8 companies that were sampled from 19 Food and Beverage Companies Listed on the Indonesian Stock Exchange. Data collection techniques through interviews and documentation. The results of data analysis using descriptive statistics, classical assumption test, simple regression test, determination test, simple linear regression test, t test, and f test so that it can be seen that working capital has a significant effect on the profitability of food and beverage industry listed on the stock exchange, capital significantly influence the profitability of food and beverage industry listed on the stock exchange, as well as working capital and capital structure have a significant effect on the profitability of food and beverage industry listed on the stock exchange.Keywords: Working Capital, Capital Structure, Profitability